How a Balinese Traditional Home Creates a Comfortable Internal Environment without Resorting to Energy Usage - I Gst. Ngr. Anom Rajendra (Pusat Kajian Bali Universitas Udayana, 2012)
AbstractBalinese traditional home is one of traditional architectures in Indonesia in which it still survives up to now. The home as a part of Balinese Traditional Architecture derives from Balinese Hindu belief and their custom which have a lot of Hindu philosophy. Base on this philosophy, the house which is created as a model of human being and a model divine of macro cosmos. The aim of this is to create harmony between micro cosmos (human being) and macro cosmos (nature). Physically, the usage of body measurements in the whole building dimensions has approved of how the implementation of a model of human being is created. Another thing is of how to abstractly create the building to have a soul through using basic dimension, mantra, and ritual for permission to the holy and devil spirit. Because of this, the building becomes a really unique thing.However, an interesting question reveals in relation to green building i.e. how does a Balinese traditional home create a comfortable internal environment without resorting energy usage? The presented paper has addressed it which is approached from the building layout to the building components. From those, the home appears that it has fully accounted to respond a warm-humid zone of the tropical climate. And a comfortable internal environment can be reached maximally through the use of open air concept or courtyard pattern in the building composition, most open and small buildings, the use of non bearing wall and also the critical point is the use of natural materials with low heat storage and large air cavity. Therefore, this means that the Balinese home has performed itself as a green building.